Development and validation by statistical treatment of stability indicating RP-HPLC method for quantification of Orlistat in Orlistat-loaded solid dispersion - Kiran Singh Sharma; Jagannath Sahoo (SpringerOpen, 2021)
Abstract Background Most of the analytical methods reported for the estimation of Orlistat were complex, expensive, and deficient in reproducibility with no or very less informative regarding various statistical methods and equations used for the validation purpose. This study provides a fast, accurate, descriptive, and precise isocratic reversed phase high-performance liquid chromatographic (HPLC) method using Waters Spherisorb 5 μm Octadecyl-silica-2 (250 × 4.6 mm) column, for the estimation of Orlistat in bulk drug and pharmaceutical formulations with minimized drug extraction steps. The drug was detected in an analytical column with mobile phase comprising a mixture of methanol, acetonitrile, and 2% phosphoric acid in the ratio of 85:14:1 v/v/v at flow rate of 1 ml/min with elution monitoring at 215.0 nm. Results The retention time for Orlistat was found to be 5.9 min with sharp and proper peak. The linearity was covered over the concentration range of 1.00-10.00 μg/ml (r 2 = 0.9997) with a limit of detection and limit of quantitation 0.06 and 0.2 μg/ml, respectively. The developed analytical technique was found to be validated for all the parameters within the acceptance criteria of ICH guidelines. The mean ± standard deviation (SD) recoveries of Orlistat were 99.87 ± 0.45. Conclusion The optimized method was well precise, accurate, sensitive, stability indicating, and tested with all statistical parameters. Thus, the method can be conveniently used in quality control and routine analysis of Orlistat containing solid dispersions and other formulations. The main advantage of the developed method was its high specificity for the estimation of Orlistat in presence of various degradation products resulting from stress conditions and formulation excipients.